2016
DOI: 10.1007/s11829-016-9420-5
|View full text |Cite
|
Sign up to set email alerts
|

Flowers promote ovarian development and vitellogenin gene expression in Apolygus lucorum (Heteroptera: Miridae)

Abstract: Apolygus lucorum (Heteroptera: Miridae), an important herbivore feeding on a broad range of cultivated and wild plants, always shows a strong preference for flowering host plants. In a prior study, we found A. lucorum fecundity to be higher on flowering plants than on plants still at the vegetative stage. This led us to hypothesize that ovarian development and vitellogenin (Vg) expression in A. lucorum, which are highly correlated with its fecundity, might respond positively to the presence of host plant flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…We cannot exclude the possibility that the reduction in dry matter accumulation results in a loss of ovary dry weight. The physiology of ovarian development is directly related to the individual's fecundity (Zhang et al ., ). The loss of female lifetime fecundity may be mainly caused by oocyte depletion, since the POP and adult longevity were not different between RNAi and control treatments.…”
Section: Discussionmentioning
confidence: 97%
“…We cannot exclude the possibility that the reduction in dry matter accumulation results in a loss of ovary dry weight. The physiology of ovarian development is directly related to the individual's fecundity (Zhang et al ., ). The loss of female lifetime fecundity may be mainly caused by oocyte depletion, since the POP and adult longevity were not different between RNAi and control treatments.…”
Section: Discussionmentioning
confidence: 97%
“…Extrafloral nectar can provide an important contribution to population growth and maintenance of the predator Iphiseius degenerans on Ricinus communis [ 49 ]. Several previous studies also reported that pollen, nectar, and honey solution were added into food of insects and were more conducive to their growth and reproduction [ 44 , 50 ]. In our previous studies, we found that rose flowers and 10% honey solution + kidney bean pods had higher soluble sugar content and protein content, while these contents were lower in rose petals and kidney bean pods [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haryati (2016) reported that A. nilaparvatae fed with honey started to emerge at the 12 th to 14 th day. The early emergence of A. nilaparvatae in the treatments of T. subulata and C. sulphureus flowers indicates that nutrients from the flowers may be able to optimize the level of vitellogenin (a precursor protein of yolk) (Zhang et al, 2016) which then increasing the maturation of eggs (Tylianakis et al, 2004). Thus, eggs hatch quickly and accelerate the process of parasitization.…”
Section: Effect Of Turnera Subulata and Cosmos Sulphureus On Parasistmentioning
confidence: 99%